2016
DOI: 10.1038/gene.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

MARCO variants are associated with phagocytosis, pulmonary tuberculosis susceptibility and Beijing lineage

Abstract: Macrophage receptor with collagenous structure (MARCO) has an important role in the phagocytosis of Mycobacterium tuberculosis (M. tuberculosis). We hypothesized that MARCO polymorphisms are associated with phagocytosis, tuberculosis (TB) disease susceptibility and presentation, and infecting lineage. We used a human cellular model to examine how MARCO genotype mediates the immune response; a case–control study to investigate tuberculosis host genetic susceptibility; and a host–pathogen genetic analysis to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…For example, beyond consistent enrichment for immune-associated GO and KEGG terms, the top 20 strongest DEG signals between the Mentawai and the Korowai include genes involved in antigen presentation in both innate and adaptive immune cells ( MARCO and SIGLEC7, respectively; MARCO p = 2.7×10 −14 ; SIGLEC7 p = 9.7×10 −14 ; these genes are also differentially expressed between Sumbanese and the Korowai ( MARCO p = 4.2×10 −10 ; SIGLEC7 p = 4.9×10 −12 ; supplementary figure 11). Polymorphisms within MARCO, which is expressed on the surface of macrophages, have been repeatedly shown to associate with susceptibility of infection by Mycobacterium tuberculosis and Streptococcus pneumoniae in multiple populations worldwide 4750 ; some of these variants have been subsequently shown to have a direct impact on antigen binding 51 . Our MethylMix analyses identify differences in SIGLEC7 expression as being driven, at least in part, by methylation differences in its promoter region (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…For example, beyond consistent enrichment for immune-associated GO and KEGG terms, the top 20 strongest DEG signals between the Mentawai and the Korowai include genes involved in antigen presentation in both innate and adaptive immune cells ( MARCO and SIGLEC7, respectively; MARCO p = 2.7×10 −14 ; SIGLEC7 p = 9.7×10 −14 ; these genes are also differentially expressed between Sumbanese and the Korowai ( MARCO p = 4.2×10 −10 ; SIGLEC7 p = 4.9×10 −12 ; supplementary figure 11). Polymorphisms within MARCO, which is expressed on the surface of macrophages, have been repeatedly shown to associate with susceptibility of infection by Mycobacterium tuberculosis and Streptococcus pneumoniae in multiple populations worldwide 4750 ; some of these variants have been subsequently shown to have a direct impact on antigen binding 51 . Our MethylMix analyses identify differences in SIGLEC7 expression as being driven, at least in part, by methylation differences in its promoter region (Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…30 This is associated with decreased expression of phagocytic molecules such as the mannose receptor, and may be restored by treatment with azithromycin, which increases the phagocytic capacity of AMs, 31 and may improve patient outcomes. 33,34 In humans, MARCO polymorphisms that reduce phagocytic capacity in monocyte-derived macrophages are linked to tuberculosis susceptibility, 33 and lower MARCO expression on AMs from diabetic mice reduces their ability to phagocytose M. tuberculosis. 33,34 In humans, MARCO polymorphisms that reduce phagocytic capacity in monocyte-derived macrophages are linked to tuberculosis susceptibility, 33 and lower MARCO expression on AMs from diabetic mice reduces their ability to phagocytose M. tuberculosis.…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…32 In mice, other phagocytic receptors, such as the macrophage receptor with collagenous structure (MARCO), are important for clearance of respiratory pathogens including Streptococcus pneumoniae and Mycobacterium tuberculosis. 33,34 In humans, MARCO polymorphisms that reduce phagocytic capacity in monocyte-derived macrophages are linked to tuberculosis susceptibility, 33 and lower MARCO expression on AMs from diabetic mice reduces their ability to phagocytose M. tuberculosis. 35 In addition to phagocytosis, AMs secrete numerous cytokines and chemokines, including interleukin-6 (IL-6), tumour necrosis factor-a, monocyte chemoattractant protein 1, RANTES and granulocyte colony-stimulating factor, which recruit other inflammatory cells.…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…hMDM were differentiated in vitro from peripheral blood monocytes (PBMCs) of PTB patients during 7 days, suggesting that these cells are inactivated or in resting stage, and their activities are not affected by other activated cell types in the patients through intercellular communication. A previous study showed no difference in phagocytic function of hMDM between TB patients and healthy volunteers; however, there was a wide range of phagocytosis abilities among individuals, which is associated with host genotype [Thuong et al., ]. There has been limited understanding of intracellular killing activities of macrophages and its variations in patients with TB.…”
Section: Discussionmentioning
confidence: 99%